A Study on the Scientific and Technological Chinese Translation by Missionary Calvin Wilson Mateer - LIU, Lanxin; REN, Dongsheng (Journal of Research for Christianity in China (JRCC), 2025)
Although widely known as an “American missionary”, “translator of the Union Mandarin Version”, and “father of modern science education in China”, Calvin Wilson Mateer has made remarkable achievements, which are by no means limited to these fields. During his forty-five years in China, he has made outstanding contributions to the development of scientific translation by translating western academic books, defining scientific terms, and putting forward translation thoughts. Thanks to his accomplishments in spreading Western culture and popularizing scientific knowledge, he was called the initiator of the modernization of Chinese science and the pioneer of cultural exchanges between China and the West. Starting from the translation of Mathletics, this paper examines his scientific and technological translation practice, analyzes his translation thoughts, summarizes his outstanding contributions in this field, and then discusses his influence on the modernization of science and technology in China, to present a different aspect of Calvin Wilson Mateer.